Law of Homicide in Nigeria. - Owoade, M. Adekunle (Obafemi Awolowo University, 2014)
The thesis analyses the ramifications of the laws relating to homicide under the Criminal and Penal Codes, and other relevant enactments in Nigeria. Owing to the origin of those Codes, particularly in their relationship with the English Common Law, comparative approach has been adopted in the study.